Residual force enhancement during multi-joint leg extensions at joint- angle configurations close to natural human motion - Paternoster, Florian Kurt; Seiberl, Wolfgang; Hahn, Daniel; Schwirtz, Ansgar (Journal of biomechanics, 2016)
The isometric steady-state forces following lengthening are greater than those produced at the same muscle length and activation level but without prior lengthening. Although residual force enhancement (RFE) has been investigated across a range of conditions, its relevance for daily human movement is still poorly understood. We aimed to study RFE in a setup imitating daily activity, i.e., submaximal activation of the lower extremity’s muscles with slightly flexed knee joints comparable to human walking. A motor-driven leg press dynamometer was used for randomly arranged purely isometric and isometric–eccentric–isometric contractions. Thirteen subjects performed multi-joint leg extensions, which were feedback-controlled at 30% of maximum voluntary vastus lateralis activation. Isometric–eccentric–isometric contractions incorporated a stretch from 30° to 50° knee flexion, while isometric contractions were performed at 50° knee flexion. Isometric contractions following stretch and purely isometric reference contractions were performed at 50° knee flexion. Kinematics, forces, and muscular activity were measured using 3D optical motion tracking, force plates, and surface EMG of 9 lower limb muscles of the right leg and joint torques were calculated by inverse dynamics. Variables of standardization (EMG, joint angles) showed no differences between contraction conditions. Eight of 13 subjects showed RFE of up to 24.8±32.5% for external forces and joint torques. Because the remaining 5 non-responders failed to produce enhanced forces during the stretch, we believe that RFE is functionally relevant for muscle function comparable to everyday human motion but only if there is enhanced force during stretch that sufficiently triggers mechanisms underlying RFE.